Designing a Model Based on the Constructive Theory According to the Integrated E-learning Pattern and Measuring its Effectiveness in Achieving Grammar Rules among Students Teachers (Arabic language major) at the Faculties of Education at Sudanese Universi - Esam Al Hassan; Ali Mohammed; Abdelrahman Ibrahim (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to design a model based on the constructive theory according to the integrated E-learning style and measure its effectiveness in the achievement of the grammatical rule for student teachers (specialization Arabic language) in the faculties of education in Sudanese universities. The researchers used developmental and quasi-experimental methods. The study population consisted of students' teachers in the fourth level (specialization Arabic language) in the faculties of education in Sudanese universities. A deliberate sample totaling 60 students was chosen from the fourth-level students in the Department of Arabic Language, Faculty of Education, the University of the Holy Quran and Islamic Sciences year 2016-2017. They were divided into two equal groups: An experimental group of thirty (30) students, and a control group of thirty (30) students. The academic tests were used as tools for data collection. By using the appropriate statistical methods, the study reached many results. The most important are: There are statistically significant differences at the level of (0.05) between means of scores of the students of the experimental group who were taught using the proposed constructive model based on integrated E-learning and means of scores of the students of the control group who were taught through the traditional method, in the post-test in favor of the experimental group. Based on these results, the researchers recommended reconsidering the teaching of Arabic language grammar courses in faculties of education by organizing and arranging their content in a manner consistent with the strategies of the constructive theory.